The Holdout : A Novel - Moore, Graham 1981- (Thorndike, Maine : Center Point Large Print, 2020)
"Its the most sensational case of the decade. Fifteen- year-old Jessica Silver, heiress to a billion-dollar real estate fortune, vanishes on her way home from school. Her teacher Bobby Nock, a twenty-five-year-old African American man, is the prime suspect after illicit text messages are discovered between them--and Jessicas blood is found in his car. The subsequent trial taps straight into Americas most pressing preoccupations: race, class, sex, law enforcement, and the lurid sins of the rich and famous. Its an open and shut case for the prosecution, and a quick conviction seems all but guaranteed. Until Maya Seale, a young woman on the jury, convinced of Nocks innocence, persuades the rest of the jurors to return the verdict of not guilty, a controversial decision that will change all of their lives forever. Flash forward ten years. A true-crime docuseries reassembles the jurors, with particular focus on Maya, now a defense attorney herself. When one of the jurors is found dead in Mayas hotel room, all evidence points to her as the killer. Now, she must prove her own innocence--by getting to the bottom of a case that is far from closed. As the present-day murder investigation weaves together with the story of what really happened during their deliberation, told by each of the jurors in turn, the secrets they have all been keeping threaten to come out--with drastic consequences for all involved"--
Keywords: Race relations -- Fiction; African Americans -- Fiction; Trials (Murder) -- Fiction; Rich people -- Fiction; Missing persons -- Investigation; Fiction; Detective and mystery fiction; Legal fiction (Literature)